Upaya Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Pendidikan agama Islam Melalui Penerapan Model Pembelajaran Probing Promting di Kelas IV SD Negeri 056006 Pematang Buluh - Raudah Raudah (Mutiara : Jurnal Penelitian dan Karya Ilmiah, 2024)
This study is motivated by the low learning outcomes of students in Islamic Religious Education at SD Negeri 056006 Pematang Buluh, which is attributed to the less varied teaching methods that fail to engage students effectively. The aim of this research is to explore and analyze the implementation of the Probing Prompting learning model in enhancing students' learning outcomes. The research method used is Classroom Action Research (CAR) conducted in two cycles, with 26 students as the subjects. Data collection was carried out through tests and observations. The results showed a significant improvement in students' learning outcomes, with the completion percentage rising from 65.38% in the pre-cycle to 80.76% in Cycle I, and reaching 96.15% in Cycle II. The application of the Probing Prompting model proved effective in increasing student engagement and understanding of the material, as well as helping them develop critical and reflective thinking skills. This study concludes that the implementation of the Probing Prompting learning model can serve as an effective strategy for enhancing the quality of education in elementary schools.